A tömjén szerepe a liturgiában - Török József; Szegedi Vallási Néprajzi Konferencia (8.) (2006) (Szeged) (2009)
All true and "real" cultures and religions need the ancient language conveyed by symbols, a language that conveys truths that are difficult to express in words. Such is the use of incense - a whole system of symbols. The burning of the incense, the smoke, the ritualistic fumigation, the sacrificial aroma - all these symbols are also present in Buddhism, as well as in Egyptian, Greek, Roman and Jewish religion; Christianity could thus not only develop its own repertoire based on this universal symbolic language, but also demarcate it. Point 1154 of the Catechism of the Catholic Church states that the use of incense is an integral part of the Liturgy of the Word. The use of incense was perhaps most poetically explained by medieval interpreters of the liturgy: the thurible represents the heart; the embers and fire inside represent love; and the rising smoke represents prayer that comes from the heart.
Keywords: Társadalomtudományok; Szociológia; Bölcsészettudományok; Filozófia, etika és vallástudományok